ON THE ESSENCE OF THE FINANCIAL FLOW - Dmitry Tokarev (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the concept of «flow-of found» and «cash flow». Influence on the modern vision of the concept of «financial flow» in Russian and foreign scientific literature. The essence of the concept of «financial flow» from the point of view of the different approaches.